3D Imaging of TiO2 nanoparticle accumulation in Tetrahymena pyriformis. (28th March 2014) - Angerer, Tina B.; Fletcher, John S.; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; Yi, Keewook; Hong, Tae Eun
<x xml:space="preserve">Abstract</x> The increasing use of nanoparticles in a wide range of applications means that there is a significant chance that these chemicals may enter the aquatic environment. We report on the use of time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) analysis to determine the 3D distribution of TiO2 nanoparticles in the fresh water dwelling single cell organism Tetrahymena pyriformis. This organism is a popular model for toxicology studies where assays normally focus on the physical behaviour of the organism (motility, proliferation etc.) or where chemical analysis has been performed on large numbers of cells that have been combined for analysis. SIMS offers the opportunity for studying this single cell organism directly. Using ToF‐SIMS analysis, the nanoparticles were shown to be accumulated in food vacuoles approximately 5 µm in diameter that are distributed throughout the cell. Challenges associated with accurate 3D reconstruction of the data because of substantial differences in sputter rate between the natural cellular material and the TiO2‐rich regions are demonstrated and discussed. Copyright © 2014 John Wiley & Sons, Ltd.